The Effect of Oil Price Shock and Exchange Rate Instability on Economic Growth in Libya For - الیاس , فوزي; علي, محمد (Dirasat in Economics and Business, 2019)
The main objective of this paper is to know the impact of the oil price shock and the instability of exchange rate on the economic growth in Libya for the period 1970-2010, employing co-integration and Vector Error Correction Model (VECM). Using time series data for the variables, oil prices, real exchange rate, and real GDP as a proxy for economic growth, the results showed that there is a balanced relationship between the variables in both long and short term. The results also showed that the impact of oil prices on growth was weak, because the Libyan government did not expand its investment spending on development projects during the period of the high oil prices in order to increase economic growth, and the impact of exchange rate has been negative on economic growth due to the rise in the value of imports.